Cell‐surface Vimentin: A mislocalized protein for isolating csVimentin+CD133− novel stem‐like hepatocellular carcinoma cells expressing EMT markers - Mitra, Abhisek; Satelli, Arun; Xia, Xueqing; Cutrera, Jeffrey; Mishra, Lopa; Li, Shulin (International journal of cancer, 2015)
Recent advances in cancer stem cell biology have shown that cancer stem‐like cells with epithelial–mesenchymal transition (EMT) phenotypes are more aggressive and cause relapse; however, absence of a specific marker to isolate these EMT stem‐like cells hampers research in this direction. Cell surface markers have been identified for isolating cancer stem‐like cells, but none has been identified for isolating cancer stem‐like cells with EMT phenotype. Recently, we discovered that Vimentin, an intracellular EMT tumor cell marker, is present on the surface of colon metastatic tumor nodules in the liver. In our study, we examined the potential of targeting cell surface Vimentin (CSV) to isolate stem‐like cancer cells with EMT phenotype, by using a specific CSV‐binding antibody, 84‐1. Using this antibody, we purified the CSV‐positive, CD133‐negative (csVim+CD133−) cell population from primary liver tumor cell suspensions and characterized for stem cell properties. The results of sphere assays and staining for the stem cell markers Sox2 and Oct4A demonstrated that csVim+CD133− cells have stem‐like properties similar to csVim−CD133+ population. Our investigation further revealed that the csVim+CD133− cells had EMT phenotypes, as evidenced by the presence of Twist and Slug in the nucleus, the absence of EpCAM on the cell surface and basal level of expression of epithelial marker E‐cadherin. The csVimentin‐negative CD133‐positive stem cells do not have any EMT phenotypes. csVim+CD133− cells exhibited more aggressively metastatic in livers than csVim−CD133+ cells. Our findings indicate that csVim+CD133− cells are promising targets for treatment and prevention of metastatic hepatocellular carcinoma. What's new? While cancer stem–like cells with epithelial–mesenchymal transition (EMT) phenotypes are known to be more aggressive and cause relapse, further advances are hampered by the absence of a specific marker. This study identifies for the first time the existence of Vimentin on the surface of liver cancer stem cells (LCSCs) and presents a separation technique to enrich EMT‐positive LCSCs directly from primary tumor cells. csVim+CD133‐ cells thus display stem‐like properties, differentiation ability, and tumorigenic properties, have the EMT phenotype, and metastasize aggressively. The findings indicate that csVim+CD133‐ cells are promising targets for treatment and prevention of metastatic hepatocellular carcinoma.